Research performance properties of fuel BIO-100 - Худолій, М.М.; Дмитриченко, М.Ф.; Вельд, Е.В.; Лабутін, М.Ю.; Батраков, В.В. (Proceedings of National Aviation University (archive), 2009)
In the article the presented results of research of operating properties of fuel BIO-100. Comparative description of operating properties of fuel presented BIO-100 and commodity petrol A-95